Penerapan Media Ular Tangga dalam Meningkatkan Hasil Belajar Fikih Peserta Didik Kelas VIII E MTs Negeri 2 Kota Surabaya - Laili Mawardi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The results of observations and interviews at MTs Negeri 2 Surabaya City showed that the achievement of the Minimum Completion Criteria (KKM) of 75 in the subject of Fiqh is still relatively low. The low learning outcomes of students are caused by the lack of focus during learning and the minimal use of learning media by teachers. The media used tend to be less varied, so that the learning process becomes monotonous and less interesting. This study aims to determine the application of snakes and ladders media in improving learning outcomes in the subject of Fiqh. The method used is Classroom Action Research (CAR) with 32 class VIII E students as research subjects. Data collection techniques are carried out through student learning outcomes and filling out observation sheets. Data are analyzed quantitatively and presented in percentage form. The results of the study show that the use of snakes and ladders media has a positive impact on improving student learning outcomes. In cycle I, the completion of learning outcomes reached 69%, and increased to 81% in cycle II. Thus, there is an increase of 12% between cycle I and cycle II. This shows that snakes and ladders media is effective in improving student learning outcomes in the subject of Fiqh.